Comprehensive genomic profiling of carcinoma of unknown primary origin: retrospective molecular classification considering the CUPISCO study design - Ross, Jeffrey S.; Sokol, Ethan S.; Moch, Holger; Mileshkin, Linda; Baciarello, Giulia; Losa, Ferran; Beringer, Andreas; Thomas, Marlene; Elvin, Julia A.; Ngo, Nhu; Jin, Dexter X.; Krämer, Alwin (The oncologist, 2021)
Background. Carcinoma of unknown primary origin (CUP) accounts for 2%-5% of newly diagnosed advanced malignancies, with chemotherapy as the standard of care. CUPISCO (NCT03498521) is an ongoing randomized trial using comprehensive genomic proﬁling (CGP) to assign patients with CUP to targeted or immunotherapy treatment arms based on genomic proﬁling. We performed a retrospective analysis of CUP cases referred for CGP to determine how many were potentially eligible for enrollment into an experimental CUPISCO arm.